2015
DOI: 10.4103/1735-1995.168384
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction state in migraine headache and neutrally mediated syncope in children and young adults

Abstract: Background:Recent evidences have supported migraine headache and neurally mediated syncope as the especial types of endotheliopathies. To determine endothelial function in patients with migraine headache or those with neurally mediated syncope, the present study was conducted.Materials and Methods:This cross-sectional study was performed on 93 consecutive patients aged 5-20 years in four groups; neurally mediated syncope, migraine, both neurally mediated syncope and migraine, and control groups. All subjects w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The few studies that found a decrease in FMD included one with an exaggerated contextual nitrate-mediated dilation, 71 one involving only MO patients, 72 and one involving CM patients. 9 Conversely, other studies found an increase in FMD in young migraine patients, 73 particularly during migraine attacks, 74 supporting the role of NO release in the induction of migraine pain. Rajan et al 75 and Larsen et al 76 (in a large population-based study) could not find any differences in FMD between migraineurs and controls.…”
Section: Resultsmentioning
confidence: 94%
“…The few studies that found a decrease in FMD included one with an exaggerated contextual nitrate-mediated dilation, 71 one involving only MO patients, 72 and one involving CM patients. 9 Conversely, other studies found an increase in FMD in young migraine patients, 73 particularly during migraine attacks, 74 supporting the role of NO release in the induction of migraine pain. Rajan et al 75 and Larsen et al 76 (in a large population-based study) could not find any differences in FMD between migraineurs and controls.…”
Section: Resultsmentioning
confidence: 94%
“…In the other study on the contrary, IMT was lower and flow-mediated dilatation of the brachial artery – another marker of vascular dysfunction – was higher (i.e. better) in 21 patients (aged 5–20 years) with migraine and 20 patients with migraine and history of syncope compared to 30 healthy controls [ 45 ]. No study has previously evaluated PWV in children with headaches.…”
Section: Discussionmentioning
confidence: 99%
“…A special pattern of inflammatory indicators has been detected in the systemic circulation in migraine patients, including increased levels of C-reactive proteins (CRP) 79 , interleukins (ILs e.g. IL-1 and IL-6) 80 , 81 , tumor necrosis factor-alpha (TNF-α) and adhesion molecules (ICAM and VCAM) 23 , 82 . These inflammatory markers disrupt the tendency of the blood cells to aggregate and lead to thrombosis and endothelial dysfunction 83 , 84 .…”
Section: Discussionmentioning
confidence: 99%
“…sVCAMs are involved in inflammation by mediating leukocyte adhesion to vascular cells 41 . CAM serum levels show elevated levels of the intracellular adhesion molecules (ICAM) and vascular cell adhesion molecules (VCAM) in children and young adults with migraine 23 , 42 , 43 .…”
Section: Introductionmentioning
confidence: 99%